Multifunctional mesoporous silica nanoparticles for cancer-targeted and controlled drug delivery - Zhang, Quan (2013)
Multifunctional mesoporous silica nanoparticles are developed in order to deliver anticancer drugs to specific cancer cells in a targeted and controlled manner. The nanoparticle surface is functionalized with amino-β-cyclodextrin rings bridged by cleavable disulfide bonds, blocking drugs inside the mesopores of the nanoparticles. Poly(ethylene glycol) polymers, functionalized with an adamantane unit at one end and a folate unit at the other end, are immobilized onto the nanoparticle surface through strong β-cyclodextrin/adamantane complexation. The non-cytotoxic nanoparticles containing the folate targeting units are efficiently trapped by folate-receptor-rich HeLa cancer cells through receptormmediated endocytosis, while folate-receptor-poor human embryonic kidney 293 normal cells show much lower endocytosis towards nanoparticles under the same conditions. The nanoparticles endocytosed by the cancer cells can release loaded doxorubicin into the cells triggered by acidic endosomal pH. After the nanoparticles escape from the endosome and enter into the cytoplasm of cancer cells, the high concentration of glutathione in the cytoplasm can lead to the removal of the β-cyclodextrin capping rings by cleaving the pre-installed disulfide bonds, further promoting the release of doxorubicin from the drug carriers. The high drug-delivery efficacy of the multifunctional nanoparticles is attributed to the co-operative effects of folate-mediated targeting and stimuli-triggered drug release. The present delivery system capable of delivering drugs in a targeted and controlled manner provides a novel platform for the next generation of therapeutics